2021
DOI: 10.1186/s12966-021-01100-3
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Global, regional, and national trends and patterns in physical activity research since 1950: a systematic review

Abstract: An amendment to this paper has been published and can be accessed via the original article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 1 publication
0
6
0
1
Order By: Relevance
“…The benefits of being physically active on health and wellbeing have been well researched and documented over the last five decades [ 1 , 2 ]. To achieve health and wellbeing benefits, the World Health Organization (WHO) provide evidence-based public health recommendations for children, adolescents, adults and older adults on the recommended frequency, intensity and duration of physical activity [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of being physically active on health and wellbeing have been well researched and documented over the last five decades [ 1 , 2 ]. To achieve health and wellbeing benefits, the World Health Organization (WHO) provide evidence-based public health recommendations for children, adolescents, adults and older adults on the recommended frequency, intensity and duration of physical activity [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…These studies identified strong correlations between CPA and physical, emotional, and intellectual development in early human life and its continued influence on wellbeing over the course of a human life, e.g., [7,8]. Along with this trend, new investigations of CPA across various regions have emphasized its diverse forms in different sociocultural and ecological contexts [9][10][11][12][13]. This study focuses on children in the pastoralist Maasai society in rural Kenya, aiming to understand the conditions of CPA in contemporary Maasai society by considering its sociocultural aspects.…”
Section: Introduction 1the Under-investigated Children In Current Physical Activity Discussionmentioning
confidence: 98%
“…To better understand CPA and its diversity, two main limitations have been well addressed in recent literature: first, the unbalanced publication coverage of study locations; second, the narrow understanding of CPA conditions outside of school, especially among less studied populations. For the former, recent systematic reviews focusing on physical activities have detected regional and national gaps in the existing studies [3,10,[13][14][15]. For instance, by focusing on the current trends of physical activity studies in relation to regional and national economic and developmental conditions, Varela et al [13] found that the most covered populations are in Europe, and the least investigated populations are in Southeast Asian and African regions.…”
Section: Introduction 1the Under-investigated Children In Current Physical Activity Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A atividade física é classicamente definida como todo e qualquer tipo de movimento realizado pelos músculos esqueléticos que induz a um gasto energético acima dos níveis de repouso . Devido as suas inúmeras contribuições na prevenção e tratamento de uma série de doenças crônicas, a atividade física se tornou foco de investigação de inúmeros pesquisadores nas últimas décadas (VARELA et al, 2021).…”
Section: Introductionunclassified